Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I think the easiest way is to calculate g(f(x)) or f(g(x)), but I don't know if it works in every case.

share|improve this question
1  
That's the definition, It does work when you can actually calculate :). A way to get a ballpark is to see if the graphs of $f$ and $g$ are a reflection of each other around the line $x=y$. –  gt6989b Nov 29 '12 at 16:25
    
You could also try taking the equation $y = f(x)$ and solving it for $x$, which will end up giving you $g(y) = x$ if $g$ is the inverse of $f$. –  Brad Nov 29 '12 at 16:27

2 Answers 2

To verify or prove that $g(x)$ is the inverse of $f(x)$, you need to show that $g(f(x)) = f(g(x)) = x$.

That is, you show both $g(f(x)) = x$ and $f(g(x)) = x$.

If you can show this, then you can conclude $g(x) = f^{-1}(x)$. (Alternatively, and equivalently, you can conclude $f(x) = g^{-1}(x)$).

share|improve this answer

If f(g(x)) = x and g(f(x)) = x, then you can say that f(x) is the g(x) inverse function.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.